A new species of Odontoglossum (Orchidaceae: oncidiinae) from Ecuador - Dalström, Stig; Merino, Gilberto (Lankesteriana: International Journal on Orchidology, 2013)
A new and horticultural desirable species of Odontoglossum from Ecuador is described, illustrated and compared with similar species.